State News Agency Frames on Terrorist Attack : Study in TVNZ New Zealand and news.lk Sri Lanka - Narayana Mahendra Prastya; Mutia Dewi (MediaTor (Jurnal Komunikasi), 2020)
Many of the global mass media tend to deliver a particular news frame in a terrorism case, especially linkage terrorism with certain religions, races, at so on. The global mass media is influenced by Western media. The news frame will be different from the news agency level. This article aims to discuss news frame by the national news agencies in New Zealand (TVNZ) and Sri Lanka (news. lk) in a terrorism case, using the Robert N. Entman frame model. The result shows TVNZ defines the problem as an unprecedented action and creates a dark history in the country, the cause of the problem is terrorists from outside New Zealand, moral judgments in the form of evidence that New Zealand society remains united, the victims are also part of the New Zealand family regardless of their background, so the recommended resolution of the problem is that the government guarantees the safety of Muslim communities. Differently, news.lk defines the problem as the motive of the attack as revenge with religious sentiment. Meanwhile, the security forces are not aware of the threat, that define the cause of the problem as the perpetrator is an organized group and an indication of religious sentiment. This media makes moral judgments by revealing the fact that Muslims not guilty, the government facilitates representatives of the religious community in Sri Lanka to express their opinions to find solutions for reconciliation and maintaining peace. The recommended resolution is that the government is ready to fight terrorism without foreign intervention, improve the performance of the security forces, and reveal the active role of the different Sri Lankan people's ethnicity and religion.